ANALYSIS OF TRENDS IN THE DEVELOPMENT OF SHARIA CAPITAL MARKET PRACTICES USING BIBLIOMETRIC ANALYSIS - M. Fauzan; Ananda Anugrah Nasution; Rendy Syaid Abdullah (RADJA PUBLIKA, 2025)
The problem of this research is:lack of exploration of the long-term impact of implementing new technologies such as cryptocurrency in Islamic capital markets, which is still not widely discussed in the current literature. The purpose of this study is to analyze publication patterns, collaboration networks between researchers, and developments in topics related to Islamic capital markets. From a theoretical perspective, there are different views regarding the effectiveness of implementing Islamic principles in responding to the ever-changing dynamics of the global market. Purpose. Data were obtained from Crossref Search for five years (2019-2024) with the keyword